Access to Justice and the Qualification Directive - Splawn, Claire (Kent Law Review, 2014)
The Qualification Directive, adopted by the Council of the European Union in 2004, creates a legal obligation for Member States to grant subsidiary protection to those persons who do not qualify for refugee status but who are in need of protection on the basis of other international obligations of Member States. An element of the Qualification Directive relates to protection from serious harm, as defined in Article 15(c) of the Directive. This article analyses the meaning and application of Article 15(c) in the UK through a selection of cases from failed Afghan asylum seekers in Kent, and identifies the difficulties courts have had in interpreting and applying the provision. It stresses the need for clarification of the terms of Article 15(c) and the impact its lack of clarity has on those applying for subsidiary protection and those in the courts adjudicating on such applications. The essay on which this article is based was awarded the Kent Law School Scott-Moncrieff Essay Prize for the best essay on social justice in 2014.